Milk Immune Cell Composition in Dromedary Camels With Subclinical Mastitis - Alhafiz, Gader Abdulaziz; Alghatam, Fatema Hassan; Almohammed, Hams; Hussen, Jamal (Frontiers in Veterinary Science, 2022)
Mastitis represents one of the most important infectious diseases in camels with heavy economic losses due to reduced milk quantity and quality. Balanced immune cell composition and function in the mammary gland are essential for effective immune response to mastitis pathogens. The objective of the present study was to characterize the cellular immune response to subclinical mastitis in the mammary gland of dromedary camels. Therefore, immunostaining and flow cytometry were used to compare the cellular composition, leukocyte phenotype, and viability in camel milk from healthy she-camels (n = 8) and she-camels with subclinical mastitis (SCM; n = 6). In addition, the ex vivo phagocytic activity of milk phagocytes was compared between healthy and affected animals. The health status of the mammary gland was evaluated based on the California Mastitis Test (CMT) score. SCM (CMT score of ≥ 3 in the absence of clinical signs of mastitis) was found in six of the 56 sampled quarters (10.7 %) with only one affected quarter per animal. In comparison to milk from healthy camels, milk from SCM animals (CMT score ≥ 3) showed higher somatic cell count (SCC), higher numbers of CD45+ leukocytes with an expanded fraction of CD172a+ myeloid cells. Within the myeloid cell population, there was an increase in the percentage of granulocytes (CD172a+CD14low) with a decreased percentage of macrophages (CD172a+CD14high) in milk from affected animals compared to healthy animals. The decrease in lymphoid cells in SCM milk was mainly due to decreased fraction of CD4+ helper T cells. Camel SCM was also associated with a stimulated phenotype, increased cell viability, and enhanced phagocytic activity of the milk phagocytes, macrophages and granulocytes. Collectively, the present study identified significant changes in SCC, leukocyte count, phenotype, viability, and function in association with subclinical mastitis in camels. The results of the present study support a better understanding of host-pathogen interaction mechanisms in the camel mammary gland.